Lightweight ANU-II block cipher on field programmable gate array - Nihad Hatif, Yousif; Amer Abbas, Yasir; Hussein Ali, Mudhafar (Institute of Advanced Engineering and Science, 2022)
Nowadays the number of embedded devices communicating over a network is increasing. Thus, the need for security appeared. Considering various constraints for the limited resources devices is very important. These constraints include power, memory, area and latency. A perfect environment for satisfying requirements of security in limited resources devices is lightweight cryptography. A recent lightweight algorithm that has a low area and high throughput which is the ANU-II block cipher. Many technologies like the internet of things (IoT) needed lightweight hardware architectures to provide security for it. In IoT issues like the size of memory, power consumption and smaller gate counts need to take care of by using lightweight cryptography. This paper presents hardware lightweight data path implementation for the ANU-II algorithm using field programmable gate array (FPGA). This paper presents a hardware implementation of a 64-bit ANU-II block cipher. Also, this research presents comparisons based on various design metrics among our data path for the ANU-II cipher and other existing data path designs. The result of the proposed design shows a high throughput of 1502.31, 1951.86, and 2696.47 Mbps. Also, it shows the high efficiency of 7.0201, 31.9977, and 10.6579 Mbps/slice as compared to other ciphers in this paper.